A Review on the Immunomodulatory Mechanism of Acupuncture in the Treatment of Inflammatory Bowel Disease. (15th January 2022) - Liu, Zhifeng; Jiao, Yi; Yu, Tianyuan; Wang, Hourong; Zhang, Yingqi; Liu, Di; Xu, Yajing; Guan, Qian; Lu, Mengqian
Abstract : Inflammatory bowel disease (IBD) is a chronic inflammatory disease with a high prevalence and canceration rate. The immune disorder is one of the recognized mechanisms. Acupuncture is widely used to treat patients with IBD. In recent years, an increasing number of studies have proven the effectiveness of acupuncture in the treatment of IBD, and some progress has been made in the mechanism. In this paper, we reviewed the studies related to acupuncture for IBD and focused on the immunomodulatory mechanism. We found that acupuncture could regulate the innate and adaptive immunity of IBD patients in many ways. Acupuncture exerts innate immunomodulatory effects by regulating intestinal epithelial barrier, toll-like receptors, NLRP3 inflammasomes, oxidative stress, and endoplasmic reticulum stress and exerts adaptive immunomodulation by regulating the balance of Th17/Treg and Th1/Th2 cells. In addition, acupuncture can also regulate intestinal flora.